2017
DOI: 10.1105/tpc.17.00370
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis MOS4-Associated Complex Promotes MicroRNA Biogenesis and Precursor Messenger RNA Splicing

Abstract: In , the MOS4-ASSOCIATED COMPLEX (MAC) is required for defense and development. The evolutionarily conserved, putative RNA helicase MAC7 is a component of the Arabidopsis MAC, and the human MAC7 homolog, Aquarius, is implicated in pre-mRNA splicing. Here, we show that, a partial loss-of-function mutant in , and two other MAC subunit mutants, and (), exhibit reduced microRNA (miRNA) levels, indicating that MAC promotes miRNA biogenesis. The mutant shows reduced primary miRNA (pri-miRNA) levels without affecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
111
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 86 publications
(146 reference statements)
8
111
0
Order By: Relevance
“…The Nuclear Cap‐Binding Complex, which affects many RNA‐related processes, including miRNA biogenesis, also responds to a wide variety of environmental conditions, processes recently reviewed by Daszkowska‐Golec (). The proteins of the MOS4‐associated complex (MAC) CDC5, PRL1 and MAC7, which interact with DCL1/SE, pri‐miRNAs and HYL1, respectively, are responsive to different stresses where they have important roles (Zhang et al ., , 2014a; Jia et al ., ). Interestingly, most of these cofactors only seem to affect subpopulations of miRNAs.…”
Section: Environmental Regulation Of the Mirna Biogenesis Machinerymentioning
confidence: 97%
See 1 more Smart Citation
“…The Nuclear Cap‐Binding Complex, which affects many RNA‐related processes, including miRNA biogenesis, also responds to a wide variety of environmental conditions, processes recently reviewed by Daszkowska‐Golec (). The proteins of the MOS4‐associated complex (MAC) CDC5, PRL1 and MAC7, which interact with DCL1/SE, pri‐miRNAs and HYL1, respectively, are responsive to different stresses where they have important roles (Zhang et al ., , 2014a; Jia et al ., ). Interestingly, most of these cofactors only seem to affect subpopulations of miRNAs.…”
Section: Environmental Regulation Of the Mirna Biogenesis Machinerymentioning
confidence: 97%
“…Being able to interact with both Pol II and DCL1, the Elongator complex might facilitate the establishment of a processing complex during transcription (Fang et al ., 2015a). Similar functions have been attributed to components of the MOS4‐associated complex (Zhang et al ., , 2014a; Jia et al ., ; Li et al ., ), a general factor that associates with the spliceosome and is conserved in plants and animals (Koncz et al ., ). After these initial events of transcription and recruitment of factors to the nascent primary transcript, the miRNA processing machinery needs to cut the stem‐loop precursor to release the small RNA.…”
Section: Microrna Processing In Plantsmentioning
confidence: 99%
“…A forkhead domain containing protein named Dawdle (DDL) is another RNA binding protein that affects miRNA accumulation by interacting with phosphorylated DCL1 and pri-miRNA, helping in the recruitment to miRNA processing complex (Yu et al, 2008;Machida and Adam Yuan, 2013). The NOT2 and MOS4-associated complex (MAC) complex members -CDC5 and PRL1 interact with components of miRNA biogenesis such as DCL1, SE, HYL1 and CBP20/80 Zhang et al, 2014Zhang et al, , 2013Jia et al, 2017). Since these components couple transcription and processing, probably these are involved in assembly of dicing bodies and recruiting pri-miRNAs to the site of primiRNA processing.…”
Section: Post-transcriptional Processing Of Pri-mirna Transcriptmentioning
confidence: 99%
“…In splicing, MAC interacts with Pol II and facilitates splicing by interacting with the spliceosome. (Reprinted from Jia et al [2017] The Plant Cell, Vol. 29: 2316-2317, October 2017, www.plantcell.org 2017 confirmed that MAC7 interacts with CDC5 and (weakly) with PRL1, but MAC7 showed no interaction with HYL1 or DCL1.…”
mentioning
confidence: 99%
“…To explore miRNA biogenesis in Arabidopsis, Jia et al (2017) screened for mutants with decreased miRNA activity in plants containing a construct that produces an artificial miRNA targeting CHLORINA42; silencing of CHLORINA42 produces bleaching along the leaf veins and mutants with decreased silencing show less bleaching (de Felippes et al, 2011). They identified a mutation in MAC7 as one of the mutants that suppressed silencing.…”
mentioning
confidence: 99%